2017
DOI: 10.1016/j.gpb.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Recent 5-Year Findings and Technological Advances in the Proteomic Study of HIV-Associated Disorders

Abstract: Human immunodeficiency virus-1 (HIV-1) mainly relies on host factors to complete its life cycle. Hence, it is very important to identify HIV-regulated host proteins. Proteomics is an excellent technique for this purpose because of its high throughput and sensitivity. In this review, we summarized current technological advances in proteomics, including general isobaric tags for relative and absolute quantitation (iTRAQ) and stable isotope labeling by amino acids in cell culture (SILAC), as well as subcellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 103 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Of note, the latest study demonstrated that the rs2093266 and rs1955656 polymorphisms in SerpinA4 and SerpinA5 genes might be risk factors for COVID-19-induced AKI (acute kidney injury) [ 26 ]. Further studies revealed that the antimicrobial activity of SerpinA5 might be attributed to its heparin-binding sequence (H-helix), and the nuclear localization signal in the H-helix was responsible for the nuclear translocation of SerpinA5 [ 27 , 28 ], implying that SerpinA5 might have a function in transcriptional regulation. However, it is not clarified yet how SerpinA5 regulates the innate immune signaling against viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the latest study demonstrated that the rs2093266 and rs1955656 polymorphisms in SerpinA4 and SerpinA5 genes might be risk factors for COVID-19-induced AKI (acute kidney injury) [ 26 ]. Further studies revealed that the antimicrobial activity of SerpinA5 might be attributed to its heparin-binding sequence (H-helix), and the nuclear localization signal in the H-helix was responsible for the nuclear translocation of SerpinA5 [ 27 , 28 ], implying that SerpinA5 might have a function in transcriptional regulation. However, it is not clarified yet how SerpinA5 regulates the innate immune signaling against viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we performed subcellular proteomic study using membrane proteins in EV71 infected RD cells. High throughout iTRAQbased proteomic technology was used [41,42], and more than 2500 proteins were quantified. Although, presently proteomics [14,21,[43][44][45][46][47] has been widely used to study EV71-affected host factors; however, in those proteomic studies, there are some limits, including using lower throughput 2DE/1DE-MS-based proteomic technology [22,43], or studying the regulated proteins in whole cells, which is difficult to detect lower abundance proteins [44,45,48].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for further investigations using “omics”‐based techniques. With the advancement of molecular technologies within the last 5–10 years (Zhang et al., 2017), there is currently no uniform pipeline for HAND biomarker/pathway discovery. There is a need to develop a consensus on a pipeline for proteomic and metabolic investigations of HAND, which increases reproducible and comparable findings across studies.…”
Section: Limitationsmentioning
confidence: 99%